Applying morpho-emergent theory to the evolution of public buildings: new design strategies for the building envelopes - Jaheen, Noha (2014)
Recent accelerating concerns about the ramifications of global warming have enhanced the need for finding unconventional solutions. The versatility and vicissitudes of nature highlight survival abilities as a main feature of the adaptation and development of organisms through time. Concurrent environmental hazards and the increasing size of construction projectshasraised the importance of buildings in terms of creating healthy conditions for users. Envelopes, as the common factors between indoor and outdoor conditions, have become the main controller of the survival process. Performance has converged between living organism shells and building shells creating morphological principles for finding solutions. The change in sequence in both macro and microclimates shows the requirement for integrating highly adaptive and responsive envelopes for buildings in the construction field. Morpho-science in the interests of both structure and behaviour was involved the consideration of new design techniques aiming to achieve better indoor environmental quality while saving energy. The aim of this dissertation is to design a multifunctional responsive building shell and to apply a depth of systematic thinking within the integration system. That led to the selection of the ‘Emilia Coccolith’ as a surviving unicellular natural concept to be analysed using aspects of morpho-genetics, morpho-structure and morpho-behaviour. Ontological and computational methods were used in simulating the selected concept to extract utilisations for designing strategies for the construction field. Generative analysis involved physical models of both ‘Hetero’ and ‘Holo’ crystals to find their lighting, ventilation and load performance to form the internal validity for this study. ANSYS and Project Falcon simulation software were used to analyse crystals at a conceptual level showing the efficiency of Holo inspired frames in discharging load per unit in contrast with identical hexagonal frames. Hetero crystals simulation pointed out the interest of crystallographic orientation and bi-refringent ability in forming advanced elements that have a special aesthetic shape which can generate synchronised movement while forming multi-directional ventilation. For the purpose of imitating the natural performance of the analysed crystals in the construction field, advanced smart materials had been involved in new innovative infill and secondary layers of the building envelope, presenting an intelligent skin which has high automation, response, dynamic and energy generative abilities. External validity was presented by examining the newly innovated shell in dry, tropical, and temperate climates using IESVE, Vasari Beta 3, Ecotec Analysis and Flow Design simulation software. Consequently the study draws a new path of design responsive efficient shells for low-rise public buildings which can achieve lighting, ventilation and thermal comfort levels while reducing energy consumption. In the different climatically selected zones of the UAE, UK and Brazil, indoor thermal comfort levels were achieved. This was seen by the envelope dry mode of 21˚C through daylight with gradual increases in humidity levels to cross 40%, especially at night when it automatically shifted the envelope to wet mode. That succeeded in reducing the cooling load in dry and tropical climates to about 44% while showing 35% for the heating load in temperate climate. Furthermore, lighting achieved the comfort level for low-rise public buildings of 2% according to ASHREA, LEED and BREEAM standards - which saved 20% lighting energy consumption. Finally, the Morpho Emergent theory was successful in designing a highly advanced breathing building skin comparable to a natural organisms’ shell while making a contribution to creating global green principles. This is important in terms of exploring sustainability awareness throughout the Middle East.